(untitled) (Al-Academy, 2026)
Time is considered one of the concepts that constitute a fundamental axis in the formation of theatre, and with the multiplicity of directing schools, there are many methods of dealing with time within the structure of the theatrical presentation. This research charts its path in four chapters. The first (methodological) chapter deals with (the research problem), which the researcher defined with the following question: (How to develop the directorial treatment according to the overlapping of tenses). The importance of the research indicates that it studies the phenomenon of multiple levels of tenses and their overlapping in theatrical presentation, and its goal is Research (detecting the overlap of tenses according to directive methods). The second chapter (theoretical framework) included two sections: the first section: (the philosophical concept of time), and the second section: (time in theatre). The third chapter included: research procedures (the research population, the method of selecting the sample, the research tools, and the research sample, which was represented by the presentation of the play (Kharif), and in the fourth chapter (the results and conclusions), the researcher presented the (results), the most prominent of which was: Time was able to express the nature of the characters, their affiliations, and their inner beings. In (Conclusions): Relying on the actor’s performance and presentation techniques to reveal the multiplicity of times and their overlap.